Studies on Polyporus abietinus. I. The enzyme-producing ability of the fungus. II. The utilization of cellulose and lignin by the fungus. III. The influence of certain factors on the rate of decay of loblolly pine sapwood. [By] Kenneth H. Garren. (1939)
Summary goes here